LENNY A. UREÑA VALERIO, Colonial Fantasies, Imperial Realities: Race Science and the Making of Polishness on the Fringes of the German Empire, 1840–1920 - Palacz, Michał Adam (LUD. Organ Polskiego Towarzystwa Ludoznawczego, 2021)
Recenzja książki Lenny A. Ureña Valerio, Colonial Fantasies, Imperial Realities: Race Science and the Making of Polishness on the Fringes of the German Empire, 1840–1920, Athens 2019.